2003
DOI: 10.1167/iovs.02-0124
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Growth and Refractive Error Development in Premature Infants without Retinopathy of Prematurity

Abstract: Most of the components of refractive status showed linear patterns of growth during this early phase of ocular development. CC displayed a more complex pattern of growth, which correlated well with refractive state. Compared with full-term infants examined around term, this group has shorter AXLs, shallower anterior chambers, and more highly curved corneas. In addition, less of the expected hypermetropia developed in the premature group, which seems mainly due to the differences in ACD and corneal curvature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 0 publications
8
57
0
6
Order By: Relevance
“…Our results are in agreement with the investigation of Cook et al (26) with regard to the development of biometric parameters in premature infants with or without retinopathy of prematurity (Figures 1-4). These authors obtained a mean axial length between 16.37 and 16.66 mm, anterior chamber depth between 2.14 and 2.26, posterior segment length between 10.18 and 10.47, and lens thickness between 3.93 and 4.04 mm.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in agreement with the investigation of Cook et al (26) with regard to the development of biometric parameters in premature infants with or without retinopathy of prematurity (Figures 1-4). These authors obtained a mean axial length between 16.37 and 16.66 mm, anterior chamber depth between 2.14 and 2.26, posterior segment length between 10.18 and 10.47, and lens thickness between 3.93 and 4.04 mm.…”
Section: Discussionsupporting
confidence: 93%
“…In another study, axial growth was measured at 3 and 9 months of age with similar findings (15) . Both birth weight and gestational age have an effect on ocular growth (26) . Saw et al (29) examined the association of birth parameters with biometry in children aged 7-9 years, and suggested that children who were born heavier or who were born more mature had longer axial lengths and deeper vitreous chambers.…”
Section: Discussionmentioning
confidence: 99%
“…24 The largest change in axial length (reflecting eye growth) occurs during the first 24 months of life, when the axial length reaches 90% of mean adult values. [24][25][26] We found that the timing of inner retinal layer regression from the fovea is consistent with the mechanical stretch hypothesis, occurring in parallel with fast eye growth and reaching completion by 17.5 months GA. Interestingly, the developmental trajectories of the inner retinal layers at the parafovea and perifovea are much more dynamic than directly at the fovea. In the case of the GCL and INL, we observed initial decreases in retinal layer thickness followed by subsequent increases.…”
Section: Discussionsupporting
confidence: 83%
“…It has also been reported that the eyes of premature infants have shallower anterior chambers, shorter axial lengths, and more highly curved corneas than full-term infants' eyes. In severe cases of ROP these differences become more significant (9) . Furthermore, children with larger head sizes or lengths at birth, or who are born heavier or more mature, have deeper vitreous chambers and longer axial lengths (16) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ROP can be a potentially blinding condition (8) . Some studies have documented alterations in ocular growth and changes in refractive errors in infants with ROP (9) . It is widely recognized that ROP is a multi-factorial condition, with gestational age, low birth weight, blood transfusion, oxygen exposure, intraventricular haemorrhage, and necrotizing enterocolitis all implicated in the disorder (10,11) .…”
Section: Introductionmentioning
confidence: 99%